Numerical Analysis of a DMA Epoxy-Carbon Composite Study - Paweł KOWALECZKO; Andrzej PANAS; Mirosław NOWAKOWSKI (Problemy Mechatroniki, 2018)
The results of numerical simulations performed for Dynamic Mechanical Analysis (DMA) measurements of thermal and mechanical (or thermomechanical) properties performed on a model composite structure are presented herein. The simulated elastic response of an epoxy-carbon fibre composite specimen was analysed for a case by which the model specimen was subjected to three-point bending with a free support. The epoxy-carbon fibre composite studied as explained herein exhibited extreme differences between the elastic properties of the epoxy resin matrix and the carbon fibre reinforcement. In addition, the carbon fibre reinforcement was both internally and structurally anisotropic. The numerical simulations were performed to demonstrate a qualitative dependence of the DMA measurement results on a certain structure of the investigated specimen and to determine if the DMA results could be qualified as effective or apparent. A macro-mechanical model of the specimen was developed and the numerical calculations were performed by applying a COMSOL/M FEM (Finite Element Method) modelling software. The carbon fibre reinforcement was modelled with an orthotropic composite structure of planar laminar inclusions or as a disperse composite with circular inclusions. While modelling different characteristic dimensions of inclusions were taken into account. Representative material properties were assumed from the results of the appropriate experimental investigations and form certain literature reference data. The effect of the composite layer configuration and their characteristic dimensions on the evaluated model elastic modulus value was also studied. The numerical modelling results are in a qualitative agreement with the results of the DMA investigations performed on real composite. They also proved the effectiveness of the developed numerical simulation methodology in modelling of micro- and macromechanical phenomena occurring during the DMA study.